(untitled) (Philosophy and Progress, 2019)
John Locke, Bishop Berkeley and David Hume are the pioneers of modern British Philosophy during 17th and 18th centuries. Among them, John Locke‟s epistemological work is one of the greatest defenses of modern empiricism. He attempts to determine the limits of human understanding and seeks to clear the ground for future developments by providing a theory of knowledge compatible with the study of human nature. In his discussion the term „ideas‟ plays an important role. To understand Locke‟s empiricism, one must realize what he means by „ideas‟. For Locke, ideas are all signs which represent the external world of physical objects and the inner world of consciousness. However, in his book, An Essay Concerning Human Understanding, he discusses „ideas‟ in details but he does not provide a sufficiently clear account of the nature of ideas. This paper is an attempt to give a critical exposition of John Locke‟s theory of ideas in which I will try to show that his explanation about the nature of idea is not sufficient enough to establish the theory of ideas he presented. Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 133-146